1972
DOI: 10.1128/jb.109.2.475-483.1972
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyribonucleic Acid Damage by Monofunctional Mitomycins and Its Repair in Escherichia coli

Abstract: Exposure of Escherichia coli to the antibiotic mitomycin C (MTC) at a concentration of 0.5 ,ug/ml caused cross-linkage between complementary strands of deoxyribonucleic acid (DNA). Derivatives of mitomycin, 7-methoxymitosene (7-MMT) and decarbamoyl mitomycin C (DCMTC), at a level as high as 20 ,ug/ml formed no cross-links between DNA strands. Ultraviolet light-sensitive mutants of E. coli K-12 bearing uvrA, uvrB, uvrC, or recA mutations were more sensitive to the lethal action of 7-MMT and of DCMTC than was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1974
1974
1988
1988

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…A 1-ml volume of the cells was removed at zero time, and the rest (1 ml) was incubated for 60 min in EM plus thymidine (20 ug/ml) medium. The cells were centrifuged, concentrated to 0.4 ml, and converted to spheroplasts, as described in a previous paper (18). Spheroplasts (10 lliters, about 107) were lysed in 0.2 ml of 0.5 N NaOH containing 0.1% sodium dodecyl sulfate in the surface layer on a 4.6-ml gradient of 5 to 20% (wt/vol) sucrose containing 10-3 M ethylenediaminetetraacetate (EDTA) and 0.9 M NaCl (adjusted to pH 12 with NaOH).…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…A 1-ml volume of the cells was removed at zero time, and the rest (1 ml) was incubated for 60 min in EM plus thymidine (20 ug/ml) medium. The cells were centrifuged, concentrated to 0.4 ml, and converted to spheroplasts, as described in a previous paper (18). Spheroplasts (10 lliters, about 107) were lysed in 0.2 ml of 0.5 N NaOH containing 0.1% sodium dodecyl sulfate in the surface layer on a 4.6-ml gradient of 5 to 20% (wt/vol) sucrose containing 10-3 M ethylenediaminetetraacetate (EDTA) and 0.9 M NaCl (adjusted to pH 12 with NaOH).…”
Section: Downloaded Frommentioning
confidence: 99%
“…The Ion-, or fil+, mutant of Escherichia coli can be assumed to be typical of such conditional division mutants, since it forms multinucleate filaments and fails to divide after low doses of UV irradiation (1,2,7,12,(22)(23)(24). To isolate a similar mutant, we have used a conventional replica plating method with mitomycin C (MTC) as a selecting agent, which has effects very similar to those of UV (5,15,18,19). By this method, we isolated two additional UVsensitive mutants of E. coli, designated RuvAand RuvB-, which formed long nonseptate filaments after very low doses of UV irradiation.…”
mentioning
confidence: 99%
“…1). In E. coli, uvrand recstrains are both Uv ' and MTC' (Iyer and Sybalski, 1963;Boyce and Howard-Flanders, 1964;Otsuji and Muramaya, 1972). If analogous repair systems exist in Synechococcus, the isolation of MTC' mutants should facilitate the isolation of strains defective in either excision or recombination repair.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that the v gene product, T4 endonuclease V, does not function to repair MC-damaged DNA. It has been shown that E. coli uvr genes, whose function can be replaced by the v gene product (14,27), are involved in repair of MC-induced damage (19). It seems of interest to see whether the apparent difference is due to different specificities of T4 and E. coli repair enzymes.…”
Section: Discussionmentioning
confidence: 99%